2015
DOI: 10.1121/1.4921027
|View full text |Cite
|
Sign up to set email alerts
|

Transfer matrix modeling and experimental validation of cellular porous material with resonant inclusions

Abstract: Porous materials are widely used for improving sound absorption and sound transmission loss of vibrating structures. However, their efficiency is limited to medium and high frequencies of sound. A solution for improving their low frequency behavior while keeping an acceptable thickness is to embed resonant structures such as Helmholtz resonators (HRs). This work investigates the absorption and transmission acoustic performances of a cellular porous material with a two-dimensional periodic arrangement of HR inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Outside this resonance, the melamine acoustic transmission loss is improved due to the added mass of the embedded HR. This effect has been presented through experimental and numerical examples that can be found in the paper by [18]. The authors concluded that it is linked to the resonance frequency of the resonator, the hosting foam size and its acoustic properties but also to the surface ratio of each component.…”
Section: Rigid Hr In Foammentioning
confidence: 93%
See 1 more Smart Citation
“…Outside this resonance, the melamine acoustic transmission loss is improved due to the added mass of the embedded HR. This effect has been presented through experimental and numerical examples that can be found in the paper by [18]. The authors concluded that it is linked to the resonance frequency of the resonator, the hosting foam size and its acoustic properties but also to the surface ratio of each component.…”
Section: Rigid Hr In Foammentioning
confidence: 93%
“…Enhancement on the acoustic performances were obtained at low frequencies. Doutres et al [18] investigated theoretically, numerically, and experimentally the acoustic absorption and transmission loss performances of a porous material with HR inclusion. An analytical model based on an extended P-TMM (Parallel transfer matrix method) has been proposed and results validated with measured and FEM (finite elements method) results.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers investigated the sound absorption performance of porous layers with embedded resonant inclusions [89][90][91][92][93][94][95][96]. Oliva and Hongisto [97] investigated and compared the accuracy of seven existing impedance prediction methods targeting the sound absorption coefficients of porous material.…”
Section: Porosity Materialsmentioning
confidence: 99%
“…Recently, the inclusion of HRs in porous material is proposed by arranging them similarly in a periodic manner [Doutres et al, 2015]. Expectedly, excellent sound attenuation is achieved but limited to the tuned resonance frequency of the resonators.…”
Section: Sound Absorption Materialsmentioning
confidence: 99%